Climate-Smart Agriculture in Mali - International Center for Tropical Agriculture; International Crops Research Institute for the Semi-Arid Tropics; United States Agency for International Development (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This Mali country Climate-Smart Agriculture profile provides a snapshot of a developing baseline created to initiate discussion, both within countries and globally, about entry points for investing in CSA at scale.